The feterminan Factors of Medical Record Employee: Employee Engagement, Competency, and Organizational Commitment - Sari, Yunita; Azizah, Queen; Rarasingtyas, Listyorini; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (Universitas Muhammadiyah Gresik, 2025)
The aim of this research is to analyze the influence of employee engagement, competency and organizational commitment on employee performance of Medical Records Installation at RSUD dr. Mohamad Soewandie Surabaya. The sample in this study were all employees of Medical Records Installation at RSUD dr. Mohamad Soewandie Surabaya numbered 47 people. The data collection technique uses a questionnaire, while the data analysis technique uses multiple linear regression. The research results prove that employee engagement, competency and organizational commitment to employee performance partially and simultaneously influence employee performance at Medical Records Installation at RSUD dr Mohamad Soewandie Surabaya. Among these three variables, organizational commitment is proven to have a dominant influence on employee performance of Medical Records Installation at RSUD dr. Mohamad Soewandie Surabaya.